LITERASI INFORMASI PENGELOLA KOMUNITAS SAHABAT ILMU JAMBI BERDASARKAN STANDAR IFLA - Rio Gusma Hendra; Wenny Dastina; Muhammad Rum (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
This study aims to determine how the ability of Jambi Friends of the Community of Friends in accessing, evaluating and using information. This study uses a qualitative research method with a descriptive approach and data collection through observation, interviews, and documentation. Data analysis techniques used: data reduction, data presentation, drawing conclusions and data triangulation. Based on the results of the analysis and research findings, the ability of the Jambi Sahabat Community Community Managers to access information based on the IFLA standard is said to be Expert, because it is seen from the manager’s ability to define information needs and to trace information through various sources, such as people who are experts in their fields, from print media: books and newspapers, electronic media: television and mobile phones. The ability of the Friends of the Jambi Friends of the Community in evaluating information based on the IFLA standard is said to be Expert, because it is seen from the ability of the manager to assess information and manage information obtained through clear sources of information, such as books, and internet media, as well as sources from internal community discussions. The ability of the Jambi Friends of the Sahabat Community Community to use information based on the IFLA standard can be said to be Expert, seen from the manager’s ability to use information and communicate information directly in the form of discussion, and indirectly as well as convey information with a simpler and easier to understand delivery